Method for preparing high nickel positive electrode material with Li2CO3, positive electrode material and application

Through the multi-stage temperature sintering method of Li2CO3 and nickel-cobalt-manganese precursor, the problem of incomplete decomposition of lithium carbonate when traditionally preparing high-nickel positive electrode materials is solved, and efficient embedding and electrochemical performance are achieved, while saving preparation costs.

CN116177621BActive Publication Date: 2025-03-28TIANJIN B&M SCI & TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310076432.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-17
Publication Date
2025-03-28
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

When traditionally using lithium carbonate to prepare ternary high-nickel cathode materials, lithium carbonate is incompletely decomposed, making it difficult for lithium ions to be embedded in the precursor, resulting in poor electrochemical performance of the cathode materials.

Method used

Multi-stage temperature sintering methods of Li2CO3 and nickel-cobalt manganese precursors are adopted, including presintering, high-temperature calcining, low-temperature calcining and re-calcining, to optimize the decomposition and intercalation effect of lithium carbonate.

Benefits of technology

Through this method, the decomposition of lithium carbonate and the effect of embedded precursors can be significantly improved, and a high-nickel positive electrode material with good electrochemical performance can be prepared, while reducing the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177621B_ABST
    Figure CN116177621B_ABST
Patent Text Reader

Abstract

This application relates to a Li 2 CO 3 Method for preparing high nickel positive electrode material, positive electrode material and application. 2 CO 3 A method for preparing a high nickel positive electrode material comprises: 2 CO 3 and a nickel-cobalt-manganese precursor to obtain a mixed raw material; pre-sintering the mixed raw material at a temperature of 450°C to 600°C; calcining the mixed raw material at a high temperature after pre-sintering at a temperature of 700°C to 1000°C; then calcining once at a low temperature, or calcining multiple times at a temperature of gradually decreasing at a temperature of 500°C to 850°C to obtain a pre-finished product; calcining the pre-finished product again at a temperature of 500°C to 800°C to obtain a high-nickel positive electrode material; the temperature of the low temperature calcination is lower than the temperature of the high temperature calcination; the nickel-cobalt-manganese precursor includes Ni x Co y Mn z (OH) 2 , where x+y+z=1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2. 2 CO 3 Method for preparing high nickel positive electrode material, capable of using Li 2 CO 3 A high-nickel positive electrode material with good electrochemical performance is prepared as a lithium source, with less lithium-nickel mixing and lower cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a high-nickel positive electrode material using Li2CO3, a positive electrode material and an application thereof. Background Art

[0002] Ternary cathode materials are generally used as cathode materials for lithium-ion secondary batteries, and are mainly used to manufacture lithium-ion batteries for new energy vehicles, power tools and other products. Ternary cathode materials have excellent electrochemical properties, including high tap density, high operating voltage, stable discharge, high specific energy, and good cycle performance. When preparing ternary cathode materials, commonly used lithium sources mainly include lithium carbonate and lithium hydroxide.

[0003] When traditionally using lithium carbonate as a lithium source to prepare ternary high-nickel positive electrode materials, the problem of incomplete decomposition of lithium carbonate is prone to occur, which makes it difficult for lithium ions to embed into the precursor, resulting in excessive lithium carbonate remaining on the surface of the positive electrode material, leading to poor electrochemical performance of the positive electrode material. Summary of the invention

[0004] Based on this, it is necessary to provide a method for preparing high-nickel positive electrode materials from Li2CO3, positive electrode materials and applications. The method for preparing high-nickel positive electrode materials from Li2CO3 has good effects of lithium carbonate decomposition and embedding precursors during the preparation process, and can prepare high-nickel positive electrode materials with good electrochemical performance.

[0005] In a first aspect, the present application provides a method for preparing a high-nickel positive electrode material from Li2CO3, comprising:

[0006] Mixing Li2CO3 and a nickel-cobalt-manganese precursor to obtain a mixed raw material;

[0007] Pre-sintering the mixed raw material at a temperature of 450° C. to 600° C.;

[0008] Pre-sintering the mixed raw material and then calcining it at a high temperature, wherein the temperature of the high temperature calcination is 700° C. to 1000° C.;

[0009] Then, a low-temperature calcination is performed once, or multiple low-temperature calcinations with gradually decreasing temperatures are performed, wherein the temperature of the low-temperature calcination is 500° C. to 850° C., to obtain a pre-finished product;

[0010] The pre-finished product is calcined again at a temperature of 500° C. to 800° C. to obtain a high-nickel positive electrode material;

[0011] The temperature of the low-temperature calcination is lower than the temperature of the high-temperature calcination;

[0012] The nickel-cobalt-manganese precursor includes Ni x Co y Mnz (OH)2, wherein x+y+z=1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2.

[0013] In some embodiments, the high temperature calcination time is 0.5h to 5h;

[0014] And / or, the low temperature calcination time is 2h to 24h;

[0015] And / or, the pre-sintering time is 3h to 5h;

[0016] And / or, the constant temperature time of the re-calcination is 1 hour to 12 hours.

[0017] In some embodiments, the mixed raw material is pre-sintered and then cooled to below 200° C. at a rate of 3° C. / min to 5° C. / min, and then calcined at high temperature.

[0018] In some embodiments, the heating rate of the high temperature calcination is 4°C / min to 6°C / min;

[0019] And / or, after the high temperature calcination, the temperature is lowered to the low temperature calcination temperature at a rate of 2°C / min to 4°C / min;

[0020] And / or, the pre-finished product is cooled from the low temperature calcination temperature to below 200° C. at a rate of 2° C. / min to 4° C. / min, and then calcined again;

[0021] And / or, the heating rate of the re-calcination is 5°C / min to 10°C / min.

[0022] In some embodiments, before calcining again, the pre-finished product after cooling is crushed and washed with deionized water. Optionally, the washing times can be one, two or three times, and vacuum drying is carried out at 120°C. The vacuum drying time is not less than 3 hours, and can be 3 hours, 5 hours, 10 hours, 15 hours, 24 hours, etc.

[0023] In some embodiments, the molar ratio n of the Li2CO3 to the nickel-cobalt-manganese precursor is 0.8<n<1.5.

[0024] In some embodiments, the mixed raw material further comprises a flux, wherein the flux comprises an inorganic salt MX, wherein M comprises Li + 、Na + , K + , Rb + and Cs + At least one of X includes F - , Cl - Br - ,I -、NO3 - and SO4 2- At least one of;

[0025] And / or, the mixed raw material also includes a doping source, and the doping source includes at least one of oxides and hydroxides of Mg, Zr, Ti, Al, Nb, Co, B, W, La, Ce, and Y.

[0026] In some embodiments, a molar ratio m of the flux to the nickel-cobalt-manganese precursor is 0≤m<0.1.

[0027] In a second aspect, the present application provides a positive electrode material prepared by any of the preparation methods described above.

[0028] In a third aspect, the present application provides a positive electrode plate, comprising a current collector and an active layer located on at least one surface of the current collector, wherein the active layer comprises the positive electrode material prepared by any of the above methods or the above positive electrode material.

[0029] In a fourth aspect, the present application provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0030] The above-mentioned method for preparing high-nickel positive electrode materials with Li2CO3 is only applicable to the preparation of high-nickel positive electrode materials using lithium carbonate as a lithium source. The method for preparing high-nickel positive electrode materials with Li2CO3 uses a multi-stage temperature sintering method to pre-sinter the mixed raw materials at 450°C to 600°C. The pre-sintering process can decompose the nickel-cobalt-manganese precursor first, which is beneficial to the increase of the contact area between the lithium source and the nickel-cobalt-manganese precursor, and can make the mixed sintering of raw materials in the subsequent sintering process better. Then high-temperature calcination is carried out at 700°C to 1000°C to promote the melting and decomposition of lithium carbonate into lithium oxide, while accelerating the lithium insertion reaction. Then low-temperature calcination is carried out at 500°C to 850°C, and the low-temperature calcination can be one stage or multiple stages to repair the lithium-nickel mixed arrangement, and finally the pre-finished product is calcined again to repair the structural damage caused by water washing to the surface of the material. Through this method, the effect of lithium carbonate decomposition and embedding precursor can be better during the preparation process, and then a high-nickel positive electrode material with good electrochemical performance can be obtained, and the cost of preparing high-nickel positive electrode materials can also be saved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of cost calculation for preparing high-nickel positive electrode material using Li2CO3 provided in one embodiment of the present application. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0034] An embodiment of the present application provides a method for preparing a high-nickel positive electrode material from Li2CO3, comprising:

[0035] Mixing Li2CO3 and a nickel-cobalt-manganese precursor to obtain a mixed raw material;

[0036] Pre-sintering the mixed raw materials at a temperature of 450° C. to 600° C.;

[0037] The mixed raw materials are pre-sintered and then calcined at a high temperature, and the temperature of the high temperature calcination is 700°C to 1000°C;

[0038] Then, a low-temperature calcination is performed once, or multiple low-temperature calcinations with gradually decreasing temperatures are performed, and the temperature of the low-temperature calcination is 500° C. to 850° C. to obtain a pre-finished product;

[0039] The pre-finished product is calcined again at a temperature of 500° C. to 800° C. to obtain a high-nickel positive electrode material;

[0040] The temperature of low-temperature calcination is lower than that of high-temperature calcination;

[0041] The nickel-cobalt-manganese precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2.

[0042] The method for preparing high-nickel positive electrode materials with Li2CO3 is only applicable to the preparation of high-nickel positive electrode materials using lithium carbonate as a lithium source. The method for preparing high-nickel positive electrode materials with Li2CO3 uses a multi-stage temperature sintering method to pre-sinter the mixed raw materials at 450°C to 600°C. The pre-sintering process can decompose the nickel-cobalt-manganese precursor first, which is conducive to increasing the contact area between the lithium source and the nickel-cobalt-manganese precursor, and can make the mixed sintering of raw materials in the subsequent sintering process better. Then, high-temperature calcination is performed at 700°C to 1000°C to promote the melting and decomposition of lithium carbonate into lithium oxide, while accelerating the lithium insertion reaction. Then, low-temperature calcination is performed at 500°C to 850°C. The low-temperature calcination can be one stage or multiple stages to repair the lithium-nickel mixed arrangement, and finally the pre-finished product is calcined again to repair the structural damage caused by water washing to the surface of the material. Through this method, the effect of lithium carbonate decomposition and embedding precursor can be better during the preparation process, so that a high-nickel positive electrode material with good electrochemical performance can be obtained, and the cost of preparing high-nickel positive electrode materials can also be saved.

[0043] Optionally, the pre-sintering temperature is 450° C., 500° C., 550° C. or 600° C. Within the pre-sintering temperature range, the nickel-cobalt-manganese precursor can be decomposed first, which is beneficial to increase the contact area between the lithium source and the nickel-cobalt-manganese precursor, and can achieve better effect of raw material mixing and sintering in the subsequent sintering process.

[0044] Optionally, the high temperature calcination temperature is 700° C., 750° C., 800° C., 850° C., 900° C., 950° C. or 1000° C. When the high temperature sintering temperature is too high, more lithium and nickel will be mixed inside the positive electrode material, resulting in reduced electrochemical efficiency of the positive electrode material. When the high temperature sintering temperature is too low, the lithium carbonate melts and decomposes into lithium oxide and accelerates the lithium insertion reaction.

[0045] Optionally, the temperature of the low-temperature calcination is 500° C., 550° C., 600° C., 650° C., 700° C., 750° C., 800° C. or 850° C. Within the temperature range of the low-temperature calcination, the repair effect on the lithium-nickel mixed arrangement is better.

[0046] Optionally, the re-calcination temperature is 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C. Within the re-calcination temperature range, the structural damage to the material surface caused by water washing can be repaired.

[0047] Optionally, x is 0.8, 0.8001, 0.801, 0.81, 0.82, 0.85, 0.9, 0.95, 0.98, 0.99, 0.999 or 1. Optionally, y is 0, 0.0001, 0.001, 0.01, 0.02, 0.05, 0.1, 0.15, 0.17, 0.19, 0.199, 0.1999 or 0.2. Optionally, z is 0, 0.0001, 0.001, 0.01, 0.02, 0.05, 0.1, 0.15, 0.17, 0.19, 0.199, 0.1999 or 0.2.

[0048] In some embodiments, multiple low-temperature calcinations are performed with the temperature decreasing successively, and the temperature of each low-temperature calcination is 500° C. to 850° C. Multiple low-temperature calcinations with the temperature decreasing successively have a better repair effect on the lithium-nickel mixed arrangement.

[0049] In some embodiments, the high temperature calcination time is 0.5h to 5h. Within the high temperature calcination time range, lithium carbonate melts and decomposes into lithium oxide, and has a good effect on accelerating the lithium insertion reaction. Optionally, the high temperature calcination time is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h.

[0050] In some embodiments, the low temperature calcination time is 2 hours to 24 hours. Within the time range of the low temperature calcination, the repair effect of the lithium nickel mixed arrangement is better. Optionally, the low temperature calcination time is 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours.

[0051] In some embodiments, the pre-sintering time is 3 hours to 5 hours. Within the pre-sintering time range, the decomposition effect of the nickel-cobalt-manganese precursor is better, which is conducive to increasing the contact area between the lithium source and the nickel-cobalt-manganese precursor, and can make the raw material mixed sintering effect in the subsequent sintering process better. Optionally, the pre-sintering time is 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.

[0052] In one embodiment, the high temperature calcination time is 0.5h to 5h, and the low temperature calcination time is 2h to 24h.

[0053] In one embodiment, the high temperature calcination time is 0.5h to 5h, and the pre-sintering time is 3h to 5h.

[0054] In one embodiment, the low-temperature calcination time is 2 hours to 24 hours, and the pre-sintering time is 3 hours to 5 hours.

[0055] In one embodiment, the low-temperature calcination time is 2 h to 24 h, and the re-calcination time is 1 h to 12 h.

[0056] In one embodiment, the high temperature calcination time is 0.5h to 5h, and the re-calcination time is 1h to 12h.

[0057] In one embodiment, the pre-sintering time is 3 h to 5 h, and the re-sintering time is 1 h to 12 h.

[0058] In one embodiment, the high-temperature calcination time is 0.5h to 5h, the low-temperature calcination time is 2h to 24h, the pre-sintering time is 3h to 5h, and the re-calcination time is 1h to 12h.

[0059] In some embodiments, the low-temperature calcination is performed multiple times, and the duration of each low-temperature calcination is 2 hours to 24 hours.

[0060] In some embodiments, before calcining again, the pre-finished product is further comprised of crushing and washing with deionized water. Optionally, the washing times may be one, two or three times, and vacuum drying is performed at 120° C. for no less than 3 hours.

[0061] In one embodiment, the pre-sintering is performed in an oxygen atmosphere.

[0062] In one embodiment, the high temperature calcination is performed in an oxygen atmosphere.

[0063] In one embodiment, the low temperature calcination is performed in an oxygen atmosphere.

[0064] In one embodiment, the re-calcination is performed under an oxygen atmosphere.

[0065] In one embodiment, the preform is subjected to a low temperature calcination.

[0066] In one embodiment, the preformed product is subjected to multiple low-temperature calcinations at successively lower temperatures.

[0067] In one embodiment, the preformed product is subjected to two low-temperature calcinations at successively lower temperatures.

[0068] In some embodiments, the mixed raw material is pre-sintered and then cooled to below 200°C at a rate of 3°C / min to 5°C / min, and then high-temperature calcination is performed. Optionally, the cooling rate of the mixed raw material to below 200°C after pre-sintering is 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min. Optionally, the mixed raw material is pre-sintered and then cooled to 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 100°C, 90°C, 80°C, 70°C, 60°C, 50°C, 40°C, 30°C or 20°C at a rate of 3°C / min to 5°C / min.

[0069] In one embodiment, before the high-temperature calcination of the mixed raw materials, the mixed raw materials are pre-sintered and then cooled to below 200° C. at a rate of 3° C. / min to 5° C. / min and then cooled to room temperature along with the furnace.

[0070] In some embodiments, the heating rate of high temperature calcination is 4°C / min to 6°C / min. Alternatively, the heating rate of high temperature calcination is 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min or 6°C / min.

[0071] In some embodiments, the high temperature calcination is followed by cooling to a low temperature calcination temperature at a rate of 2°C / min to 4°C / min. Optionally, the cooling rate from the high temperature calcination to the low temperature calcination temperature is 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min or 4°C / min.

[0072] In some embodiments, before the pre-finished product is calcined again, the pre-finished product is cooled from the low temperature calcination temperature to below 200°C at a rate of 2°C / min to 4°C / min. Optionally, the cooling rate of the pre-finished product from the low temperature calcination temperature to below 200°C is 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min or 4°C / min. Optionally, the pre-finished product is cooled from the low temperature calcination temperature to 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 100°C, 90°C, 80°C, 70°C, 60°C, 50°C, 40°C, 30°C or 20°C at a rate of 2°C / min to 4°C / min.

[0073] In one embodiment, before the pre-finished product is calcined again, the pre-finished product is cooled from the low-temperature calcination temperature to below 200° C. at a rate of 2° C. / min to 4° C. / min and then cooled to room temperature in the furnace.

[0074] In some embodiments, the heating rate of the re-calcination is 5°C / min to 10°C / min. Alternatively, the heating rate of the re-calcination is 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min or 10°C / min.

[0075] In one embodiment, the room temperature is 20°C to 35°C.

[0076] In some embodiments, the molar ratio n of Li2CO3 to the nickel-cobalt-manganese precursor is 0.8<n<1.5. Optionally, the molar ratio of Li2CO3 to the nickel-cobalt-manganese precursor is 0.8, 0.8001, 0.801, 0.81, 0.83, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1, 1.1, 1.2, 1.3, 1.4, 1.42, 1.45, 1.47, 1.49, 1.499, 1.4999 or 1.5.

[0077] In some embodiments, the mixed raw material further comprises a flux, and the flux comprises an inorganic salt MX, wherein M comprises Li + 、Na + , K + , Rb + and Cs + At least one of X includes F - , Cl - Br - ,I - 、NO3 - and SO4 2- Adding flux can make the melting and mixing of mixed raw materials more uniform during sintering, and the sintering effect is better.

[0078] In some embodiments, the molar ratio m of the flux to the nickel-cobalt-manganese precursor is 0≤m<0.1. Within the molar ratio range of the flux to the nickel-cobalt-manganese precursor, the flux has a better fluxing effect. Optionally, the molar ratio of the flux to the nickel-cobalt-manganese precursor is 0, 0.0001, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.099, 0.0999 or 0.1.

[0079] In some embodiments, the mixed raw material further includes a doping source, and the doping source includes at least one of oxides and hydroxides of Mg, Zr, Ti, Al, Nb, Co, B, W, La, Ce, and Y.

[0080] In one embodiment, the method for preparing high nickel positive electrode material from Li2CO3 is as follows:

[0081] Mixing Li2CO3 and a nickel-cobalt-manganese precursor to obtain a mixed raw material;

[0082] Pre-sintering the mixed raw materials at a temperature of 450° C. to 600° C.;

[0083] The mixed raw materials are pre-sintered and then calcined at a high temperature, and the temperature of the high temperature calcination is 700°C to 1000°C;

[0084] Then, multiple low-temperature calcinations are performed with gradually decreasing temperatures, and the temperature of the low-temperature calcinations is 500° C. to 850° C. to obtain a pre-finished product;

[0085] The pre-finished product is calcined again at a temperature of 500° C. to 800° C. to obtain a high-nickel positive electrode material;

[0086] The temperature of low-temperature calcination is lower than that of high-temperature calcination;

[0087] The nickel-cobalt-manganese precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2.

[0088] In one embodiment, the method for preparing high nickel positive electrode material from Li2CO3 is as follows:

[0089] Mixing Li2CO3 and a nickel-cobalt-manganese precursor to obtain a mixed raw material;

[0090] Pre-sintering the mixed raw materials at a temperature of 450° C. to 600° C.;

[0091] The mixed raw materials are pre-sintered and then calcined at a high temperature, and the temperature of the high temperature calcination is 700°C to 1000°C;

[0092] Then, a low-temperature calcination is performed at a temperature of 500°C to 850°C to obtain a pre-finished product;

[0093] The pre-finished product is calcined again at a temperature of 500° C. to 800° C. to obtain a high-nickel positive electrode material;

[0094] The temperature of low-temperature calcination is lower than that of high-temperature calcination;

[0095] The nickel-cobalt-manganese precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2.

[0096] Another embodiment of the present application provides a positive electrode material prepared by any of the above methods.

[0097] Another embodiment of the present application provides a positive electrode plate, including a current collector and an active layer located on at least one surface of the current collector, the active layer including a high-nickel positive electrode material prepared by any of the above preparation methods or the above positive electrode material.

[0098] Another embodiment of the present application provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0099] The following are specific embodiments

[0100] Example 1

[0101] Take Li2CO3 (783.2 g, 10.6 mol) and Ni 0.95 Co 0.02 Mn 0.03 (OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, which was then transferred to a sagger and heated to 500°C at a heating rate of 4°C / min in an oxygen atmosphere, kept constant for 4 hours, cooled to below 200°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace. Then, the mixture was heated to 950°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 2 hours, cooled to 750°C at a cooling rate of 3°C / min, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a pre-finished high-nickel positive electrode material. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature and passed through a 325-mesh sieve to obtain a high-nickel positive electrode material.

[0102] Electrochemical test: The positive electrode material obtained in Example 1 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0103] Example 2

[0104] Take Li2CO3 (783.2 g, 10.6 mol), ZrO (12.3 g, 0.1 mol) and Ni 0.95 Co 0.02 Mn 0.03 (OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, which was then transferred to a sagger and heated to 500°C at a heating rate of 4°C / min in an oxygen atmosphere, kept constant for 4 hours, cooled to below 200°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace. Then, the mixture was heated to 950°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 2 hours, cooled to 750°C at a cooling rate of 3°C / min, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a pre-finished high-nickel positive electrode material. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature and passed through a 325-mesh sieve to obtain the positive electrode material.

[0105] Electrochemical test: The high nickel positive electrode material obtained in Example 2 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0106] Example 3

[0107] Take Li2CO3 (783.2 g, 10.6 mol), ZrO (12.3 g, 0.1 mol) and Ni 0.95 Co 0.02 Mn 0.03(OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, which was then transferred to a sagger and heated to 500°C at a heating rate of 4°C / min in an oxygen atmosphere, kept constant for 4 hours, cooled to below 200°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace. Then, the mixture was heated to 950°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 2 hours, cooled to 750°C at a cooling rate of 3°C / min, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a pre-finished high-nickel positive electrode material. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature and passed through a 325-mesh sieve to obtain the positive electrode material.

[0108] Electrochemical test: The high nickel positive electrode material obtained in Example 3 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0109] Example 4

[0110] Take Li2CO3 (783.2 g, 10.6 mol), ZrO (12.3 g, 0.1 mol) and Ni 0.95 Co 0.02 Mn 0.03(OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, which was then transferred to a sagger and heated to 500°C at a heating rate of 4°C / min in an oxygen atmosphere, kept constant for 4 hours, cooled to below 200°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace. Then, the mixture was heated to 980°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 2 hours, cooled to 750°C at a cooling rate of 3°C / min, kept constant for 10 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a pre-finished high-nickel positive electrode material. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature and passed through a 325-mesh sieve to obtain the positive electrode material.

[0111] Electrochemical test: The high nickel positive electrode material obtained in Example 4 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0112] Example 5

[0113] Take Li2CO3 (783.2 g, 10.6 mol), NaCl (29.2 g, 0.5 mol) and Ni 0.95 Co 0.02 Mn 0.03(OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, which was then transferred to a sagger and heated to 500°C at a heating rate of 4°C / min in an oxygen atmosphere, kept constant for 4 hours, cooled to below 200°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace. Then, the mixture was heated to 950°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 2 hours, cooled to 750°C at a cooling rate of 3°C / min, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a pre-finished high-nickel positive electrode material. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature and passed through a 325-mesh sieve to obtain the positive electrode material.

[0114] Electrochemical test: The high nickel positive electrode material obtained in Example 5 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0115] Example 6

[0116] Take Li2CO3 (783.2 g, 10.6 mol), ZrO (12.3 g, 0.1 mol) and Ni 0.95 Co 0.02 Mn 0.03(OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, which was then transferred to a sagger and heated to 500°C at a heating rate of 4°C / min in an oxygen atmosphere, kept constant for 4 hours, cooled to below 200°C at a cooling rate of 4°C / min, and then cooled to room temperature with the furnace. Then, the mixture was heated to 950°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 2 hours, cooled to 800°C at a cooling rate of 3°C / min, kept constant for 2 hours, cooled to 750°C at a cooling rate of 3°C / min, kept constant for 15 hours, and finally cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a pre-finished high-nickel positive electrode material. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature and passed through a 325-mesh sieve to obtain the positive electrode material.

[0117] Electrochemical test: The high nickel positive electrode material obtained in Example 6 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0118] Comparative Example 1

[0119] Take Li2CO3 (387.9 g, 5.3 mol) and Ni 0.95 Co 0.02 Mn 0.03 (OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, and the mixture was transferred to a sagger, heated to 750°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a high-nickel positive electrode material pre-finished product. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, and then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a high-nickel positive electrode material.

[0120] Electrochemical test: The high nickel positive electrode material obtained in Comparative Example 1 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0121] Comparative Example 2

[0122] Take Li2CO3 (387.9 g, 5.3 mol) and Ni 0.95 Co 0.02 Mn 0.03 (OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, and the mixture was transferred to a sagger, heated to 950°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a high-nickel positive electrode material pre-finished product. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, and then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a high-nickel positive electrode material.

[0123] Electrochemical test: The high nickel positive electrode material obtained in Comparative Example 2 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0124] Comparative Example 3

[0125] Take LiOH·H2O (440.6 g, 10.6 mol) and Ni 0.95 Co0.02 Mn 0.03 (OH)2 (926.0 g, 10 mol) was added to a V-type mixer and mixed for 3 hours to obtain a mixture, and the mixture was transferred to a sagger, heated to 750°C at a heating rate of 5°C / min in an oxygen atmosphere, kept constant for 15 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature to obtain a high-nickel positive electrode material pre-finished product. The high-nickel positive electrode material pre-finished product was crushed and washed once with deionized water, vacuum dried at 120°C for 3 hours, and then heated to 700°C at a heating rate of 10°C / min, maintained for 6 hours, cooled to below 200°C at a cooling rate of 3°C / min, and then naturally cooled to room temperature, and passed through a 325-mesh sieve to obtain a high-nickel positive electrode material.

[0126] Electrochemical test: The high nickel positive electrode material obtained in comparative example 3 was mixed with conductive carbon and PVDF (polyvinylidene fluoride) binder in a ratio of 90:5:5 (mass ratio) in NMP (N-methylpyrrolidone) and then coated on aluminum foil to obtain a pole piece. After the pole piece was dried in a blast oven at 80°C, it was placed in a vacuum oven at 120°C and dried overnight. The dried pole piece was used as the positive electrode of the battery, lithium metal as the negative electrode of the battery, a single-layer polyethylene film as the diaphragm, and 1M LiPF6-EC-EMC (i.e., the concentration of LiPF6 in EC-EMC solvent is 1M, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and the volume ratio of EC:EMC is 3:7) as the electrolyte, and assembled into a 2032 battery for electrochemical testing.

[0127] The test results of the lithium nickel mixing values ​​in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1 below:

[0128] Table 1

[0129] serial number Percentage of nickel in lithium position (%) Example 1 0.9 Example 2 0.9 Example 3 1.1 Example 4 1.5 Example 5 0.9 Example 6 1.0 Comparative Example 1 1.1 Comparative Example 2 4.2 Comparative Example 3 1.0

[0130] The batteries assembled from Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to electrochemical tests. The test method was as follows: the battery was tested using a constant current charge and discharge tester. The test conditions were 25°C, 2.8-4.3V vs Li + / Li, the first cycle was tested at a rate of 0.1C charge / 0.1C discharge, and the subsequent 50 cycles were tested at a rate of 1C charge / 1C discharge. The first discharge specific capacity, first coulombic efficiency and 50 cycle capacity retention rate are shown in Table 2:

[0131] Table 2

[0132]

[0133]

[0134] At the same time, refer to Figure 1The cost of preparing high-nickel positive electrode materials in Examples 1 to 6 and Comparative Examples 1 to 3 is calculated, and the calculation assumptions are: price of lithium hydroxide monohydrate: 568,000 yuan / ton (battery grade / micro powder); price of lithium carbonate: 573,250 yuan / ton (battery grade), and the chemical composition of high-nickel ternary materials is LiNi 0.9 Co 0.05 Mn 0.05 O2, lithium source / precursor feed molar ratio is 1.06.

[0135] In Examples 1 to 6, by controlling the temperature of multi-stage calcination, it is possible to use only lithium carbonate as a lithium source to prepare a high-nickel positive electrode material, which can save costs. At the same time, the battery assembled with the positive electrode materials in Examples 1 to 6 also has good first discharge specific capacity, first coulomb efficiency and 50 cycle capacity retention rate.

[0136] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0137] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.

Claims

1. A method for preparing high nickel positive electrode material from Li2CO3, characterized in that: include: Mixing Li2CO3 and a nickel-cobalt-manganese precursor to obtain a mixed raw material; Pre-sintering the mixed raw material, wherein the pre-sintering temperature is 450° C. to 600° C., and the pre-sintering constant temperature time is 3 h to 5 h; After pre-sintering the mixed raw material, the temperature is lowered to below 200° C. at a rate of 3° C. / min to 5° C. / min, and then cooled to room temperature with the furnace, and then high-temperature calcination is performed, wherein the temperature of the high-temperature calcination is 700° C. to 1000° C., and the holding time of the high-temperature calcination is 0.5 h to 5 h; After high-temperature calcination, the temperature is lowered to a low-temperature calcination temperature at a rate of 2°C / min to 4°C / min, and then a low-temperature calcination is performed once, or multiple low-temperature calcinations with gradually decreasing temperatures are performed, each of which is performed at a temperature of 500°C to 850°C, and the constant temperature time of each low-temperature calcination is 2h to 24h, to obtain a pre-finished product; The pre-finished product is cooled from the low temperature calcination temperature to below 200°C at a rate of 2°C / min to 4°C / min and then cooled to room temperature along with the furnace; crushing the pre-finished product and washing it with deionized water; The pre-finished product is calcined again, the calcination temperature is 500° C. to 800° C., and the constant temperature time of the re-calcination is 1 hour to 12 hours to obtain a high-nickel positive electrode material; The temperature of the low-temperature calcination is lower than the temperature of the high-temperature calcination; The nickel-cobalt-manganese precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, 0.8001≤x≤1, 0≤y≤0.2, 0≤z≤0.

2.

2. The method for preparing high-nickel positive electrode material from Li2CO3 according to claim 1, characterized in that: The heating rate of the high temperature calcination is 4°C / min to 6°C / min; And / or, the heating rate of the re-calcination is 5°C / min to 10°C / min.

3. The method for preparing high-nickel positive electrode material from Li2CO3 according to claim 1, characterized in that: The molar ratio n of the Li2CO3 to the nickel-cobalt-manganese precursor is 0.8<n<1.

5.

4. The method for preparing high-nickel positive electrode material from Li2CO3 according to any one of claims 1 to 3, characterized in that: The mixed raw material also includes a flux, and the flux includes an inorganic salt MX, wherein M includes Li + 、Na + , K + , Rb + and Cs + At least one of X includes F - , Cl - Br - ,I - 、NO3 - and SO4 2- At least one of .

5. The method for preparing high-nickel positive electrode material from Li2CO3 according to claim 4, characterized in that: The molar ratio m of the flux to the nickel-cobalt-manganese precursor is 0≤m<0.

1.

6. The method for preparing high-nickel positive electrode material from Li2CO3 according to any one of claims 1 to 3, characterized in that: The mixed raw material also includes a doping source, which includes at least one of oxides and hydroxides of Mg, Zr, Ti, Al, Nb, Co, B, W, La, Ce, and Y.

7. A positive electrode material, characterized in that: It is prepared by the method according to any one of claims 1 to 6.

8. A positive electrode sheet, characterized in that: It comprises a current collector and an active layer located on at least one surface of the current collector, wherein the active layer comprises the positive electrode material prepared by the method described in any one of claims 1 to 6 or the positive electrode material described in claim 7.

Citation Information

Patent Citations

  • Preparation method of high-performance cobalt nickel lithium manganate ternary material

    CN103682306A

  • High-nickel ternary positive electrode material and preparation method thereof, lithium ion battery and electric vehicle

    CN111422925A